2020
DOI: 10.1111/cas.14657
|View full text |Cite
|
Sign up to set email alerts
|

Isatuximab monotherapy in relapsed/refractory multiple myeloma: A Japanese, multicenter, phase 1/2, safety and efficacy study

Abstract: Isatuximab, an anti‐CD38 monoclonal antibody, targets cells that strongly express CD38 including malignant plasma cells. This open‐label, single‐arm, multicenter, phase 1/2 trial investigated the tolerability/safety and efficacy of isatuximab monotherapy in Japanese patients with heavily pretreated, relapsed/refractory multiple myeloma (RRMM). In Phase 1, patients were sequentially assigned to receive isatuximab once weekly (QW) in cycle 1 (4 weeks) and every 2 weeks (Q2W) in subsequent cycles. Cohort 1 (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…The 20-mg/kg dosing regimen was assessed in the phase I/II ISLAND study in Japanese patients with RRMM, whose results demonstrated a 36.4% ORR (12/33 patients). 29 For Isa-Rd, model predictions confirmed, similar to the monotherapy study, that regimens initiated with weekly dosing for cycle 1 (QW4-Q2W) induced a greater reduction in M-protein levels compared with Q2W dosing. However, simulations revealed that increasing the isatuximab dose from 10 to 20 mg/kg does not significantly affect M-protein reduction (Figure 2).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The 20-mg/kg dosing regimen was assessed in the phase I/II ISLAND study in Japanese patients with RRMM, whose results demonstrated a 36.4% ORR (12/33 patients). 29 For Isa-Rd, model predictions confirmed, similar to the monotherapy study, that regimens initiated with weekly dosing for cycle 1 (QW4-Q2W) induced a greater reduction in M-protein levels compared with Q2W dosing. However, simulations revealed that increasing the isatuximab dose from 10 to 20 mg/kg does not significantly affect M-protein reduction (Figure 2).…”
Section: Discussionsupporting
confidence: 55%
“…The 20-mg/kg dosing regimen was assessed in the phase I/II ISLAND study in Japanese patients with RRMM, whose results demonstrated a 36.4% ORR (12/33 patients). 29 F I G U R E 1 Model predictions of M-protein profiles under different isatuximab dose regimens. Q2W, administration every 2 weeks; QW4-Q2W, weekly administration for 4 weeks followed by every 2 weeks thereafter | 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current clinical practice uses monoclonal anti-CD38 antibodies, such as Daratumumab ( 309 , 310 ) or Isatuximab ( 311 , 312 ), in combination with a PI and IMiDs as standard upfront therapy ( 313 ). Given the fact that PI-induced mitochondrial trafficking between BMSCs and MM PCs is a CD38-dependent process ( 75 ), this provides a solid biological rational for combining PIs in triplet/quadruplet therapies as per current practice.…”
Section: Overcoming Tme-mediated Pi Resistancementioning
confidence: 99%